Musik und Dichtung : Das musikalische Element in der Lyrik Pasternaks - Fischer, Christine (1998)
Subject of this essay is the investigation of the relationship between music and poetry in the poetry of Pasternak. In the main part then the meaning of music in Pasternak's poetry is to be examined in a double sense - on technical-stylistic and on motivic level, where in the first area in addition to the formative means of poetry (such as metric, rhyming and stanza forms) and certain methods of special coupling be analyzed by sound and meaning. The second part of the main part, in addition to the "real" music history in Pasternak's poetry (such as the mention of composer names and musical instruments), includes the study of literary leitmotifs associated with music, such as birds, wind, water, sound and silence...